Relationship Between Hypertension and Basilar Atherosclerosis in Chinese Han Population: A High-Resolution Magnetic Resonance Imaging Study - Hu, Feng; Lu, Feng; Xiao, Huiling; Dong, Meixue; Xu, Yan (Frontiers in Cardiovascular Medicine, 2022)
Objective: To investigate the relationship between hypertension and basilar atherosclerosis evaluated by high-resolution magnetic resonance imaging (HR-MRI) in Chinese Han population. Methods: HR-MRI vessel wall imaging was performed in selected 193 patients for various indications. Multivariable logistic regression models based on odds ratio (OR) with their associated 95% confidence interval (CI) were used to assess the relationship between hypertension and basilar artery (BA) plaque, moderate-severe stenosis of BA plaque as well as vulnerable plaque. Linear regression model was used to assess the relationship between hypertension and BA plaque numbers. Results: Hypertension patients had a higher proportion of BA plaque and vulnerable plaque, more numbers of BA plaque and serious plaque enhancement compared to normotensive (all P-value <0.05). Multivariable logistic regression analysis indicated that hypertension patients had increased risk for BA plaque and its numbers (adjusted-OR: 4.32, 95% CI 1.89 to 9.88, P <0.001; adjusted-β: 0.55, 95% CI 0.14 to 0.96, P =0.009, respectively), had a higher proportion of moderate-severe stenosis of BA plaque and vulnerable plaque (adjusted-OR: 3.08, 95% CI 0.77 to 12.32, P =0.111; adjusted-OR: 4.52, 95% CI 1.50 to 13.64, P =0.007, respectively) compared to normotensive group. Moreover, there were a saturation effect of age on the prevalence of BA plaque and vulnerable plaque. Conclusion: Hypertension was the independent risk factor of BA plaque and vulnerable plaque assessed by HR-MRI in Chinese Han population.